Innovation in a podshell: bringing information literacy into the world of podcasting - Berk, J.; Olsen, Sonja; Atkinson, Jody; Comerford, Joanne (Emerald Group Publishing Limited, 2007)
Purpose – This paper seeks to examine the development of a pilot program for using podcasting as a tool in the provision of information literacy in an academic library. It aims to discuss the implementation process and the issues encountered in developing a podcasting series at the Curtin University Library. Design/methodology/approach – The possibilities for using podcasts to deliver library information literacy in an academic library are discussed in reference to current literature and trends. The method for creating a podcasting series, including the equipment, software, RSS feed, legal issues and cost and staffing implications, is outlined along with the parameters used by the Curtin University Library in the development of a pilot series. Findings – The paper finds that podcasts offer libraries a new method of delivering information literacy to their clients. It is possible to create a podcasting series with minimal expense and the simple production method enables many libraries to take advantage of this new technology. The podcasting series at Curtin has proven to be popular with downloads increasing steadily over the course of the semester. There have been over 9,000 downloads of the audio files to the end of November 2006. By taking advantage of this ubiquitous technology libraries can communicate with their clientele in a new and exciting way. Originality/value – The paper outlines how to create a podcasting series for information literacy in an academic library environment, and provides recommendations for other libraries wishing to create their own podcasting series.